1001 Home Remedies & Natural Cures - Floyd, Esme (Carlton, 2012)
Includes at-home solutions that can help treat everything from first-aid emergencies to chronic health conditions. This book offers drug-free relief with kitchen cures for common ailments and injuries which range from traditional herbalist ideas through food-based immune-boosters to household concoctions
Include Index
Keywords: Naturopathy -- Popular works -- Naturopathy